Pengembangan Sistem Informasi Inventaris Barang Desa Kabukarudi Berbasis Web - Karolus Wulla Rato; Aderbertus Umbu Jangga; Bole Pati, Arianto (Universitas Medan Area, 2023)
Along with the development of a government institution or agency at this time, the number of assets needed and must be owned by the institution or agency is also increasing. For this reason, assets need good management so that they are easier to monitor and manage. In solving this problem, it is necessary to have a system that assists in managing government assets. An asset management system can assist in managing asset data such as providing transparent and continuous reports. As an approach to designing an asset management system, the author uses direct observation, interviews and literature, created using the programming language PHP Hypertext Preprocessor, Object-Oriented Programing (OOP), system development using the SDLC waterfall method and the database used is MySQL which will be executed on the Windows 10 operating system. In designing the asset management system there are 2 (two) users, namely Admin and Wasapras. Admin and Wasapras have full access rights to the system.